1989
DOI: 10.1007/bf01359557
|View full text |Cite
|
Sign up to set email alerts
|

Definition of carcinoma of the gastric cardia

Abstract: This study concerns the definition of carcinoma of the gastric cardia. The topography of the esophagogastric mucosal junction (mucosal EGJ) was investigated with an endoscope in 182 patients who were free of hiatal hernias, ulcers, and neoplasms in the esophagus and stomach. The relationship between the EGJ and the cardiac gland area was then examined histologically in 56 resected specimens containing intact EGJs and cardia gland areas. Furthermore the cancerous center was determined; the shortest distance bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 16 publications
1
39
1
Order By: Relevance
“…Previous studies have shown an increased risk of distal gastric cancer for H. pylori -seropositive subjects compared with seronegative subjects, whereas no association was observed among upper third gastric cancer (25)(26)(27) but not all (23,36,37). The discrepancy in results between studies may, to some extent, be due to different levels of misclassification of cardia cancers, such as the recent introduction of a separate diagnostic code, the lack of consensus for a definition of cardia, and an increased interest in cardia cancers (38,39). The definition of cardia cancer (upper third) was more inclusive than most definitions used outside Japan and would include NOTE: Pepsinogen index (À), pepsinogen I >70 or pepsinogen I/II ratio >3; (+), pepsinogen I V70 and pepsinogen I/II ratio V3, excluding pepsinogen index 2+ and 3+; (2+), pepsinogen I V50 and pepsinogen I/II ratio V3, excluding pepsinogen index 3+; (3+), pepsinogen I V30 and pepsinogen I/II ratio V2.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown an increased risk of distal gastric cancer for H. pylori -seropositive subjects compared with seronegative subjects, whereas no association was observed among upper third gastric cancer (25)(26)(27) but not all (23,36,37). The discrepancy in results between studies may, to some extent, be due to different levels of misclassification of cardia cancers, such as the recent introduction of a separate diagnostic code, the lack of consensus for a definition of cardia, and an increased interest in cardia cancers (38,39). The definition of cardia cancer (upper third) was more inclusive than most definitions used outside Japan and would include NOTE: Pepsinogen index (À), pepsinogen I >70 or pepsinogen I/II ratio >3; (+), pepsinogen I V70 and pepsinogen I/II ratio V3, excluding pepsinogen index 2+ and 3+; (2+), pepsinogen I V50 and pepsinogen I/II ratio V3, excluding pepsinogen index 3+; (3+), pepsinogen I V30 and pepsinogen I/II ratio V2.…”
Section: Discussionmentioning
confidence: 99%
“…Tumors were initially classified by anatomic site, using the Siewert classification system, one of the most commonly used anatomic classification systems for tumors of the esophagogastric junction. 3,18,19 This system includes only tumors arising within 5 cm of the esophagogastric junction, and defines the anatomic esophagogastric junction as the site where the proximal gastric rugal folds terminate and the tubular esophagus begins. Type 1 tumors are those arising with their epicenter within 1-5 cm proximal to the esophagogastric junction, whereas type 3 arise within 2-5 cm distal to the esophagogastric junction, and are considered to represent tumors of the subcardia that have spread into the esophagogastric junction from below.…”
Section: Patient Populationmentioning
confidence: 99%
“…Cancer of the gastric cardia (n ϭ 20) was defined as an adenocarcinoma with its center located within 1 cm proximal and 2 cm distal to the gastroesophageal junction. 31 Adenocarcinoma of the antrum or body or fundus was defined as a noncardia cancer (n ϭ 214).…”
Section: Clinical Characteristicsmentioning
confidence: 99%